Nocturnal Mammals of Segaliud-Lokan Forest Reserve, Sabah - Kee, Sze-Lue; Jephte Sompud; Pei, Kurtis Jai-Chyi; Mahmud Sudin; Collin Goh; Paul Liau; Fadzil Yahya (e-VIBS, Faculty of Science and Natural Resources, 2018)
The aim of this study is to document the population density and diversity of nocturnal mammal in Segaliud-Lokan Forest Reserve (SLFR). Vehicle spotlight survey was conducted from October – December 2017. A total distance of 1,720 km travelled along the gravel roads. There were 24 species with 14 families (195 sighting) nocturnal mammals were recorded. Many large nocturnal mammals can be found in Segaliud-Lokan Forest Reserve, including Asian elephant (Elephas maximus), Tembadau (Bos javanicus), and Clouded leopard (Neofelis diardi). The Shannon’s diversity index and Simpson diversity index were 2.60 and 0.90, respectively. King's census method was used to estimate the population density which was 4.780 individual per square kilometer. The population density and diversity of nocturnal mammals was high, indicating that the forest operations in SLFR seemingly support the sustainability of the nocturnal mammal population there.